Baby Spa On The Quality Of Sleep Baby In Les Bubbles Exclusive For Mom, Baby And Kids Medan - Antonij Sitanggang; Flora Sijabat; Marthalena Simamora; Julia Darwin Panjaitan (Institute of Computer Science (IOCS), 2022)
Sleep is basic need that is required by all human beings to be able to optimally function both healthy and diseased. One effort that can be done to help improve the quality of sleep is to Baby Spa.This study aims to determine the effect of baby spa on the quality of sleep in infants at Les Bubbles Exclusive For Mom, Baby & Kids Medan. This type of research is Quasi-Experiment with One group pre-post design research design. The population in this study were mothers who had babies aged 1-6 months the first visit at Les Bubbles Exclusive For Mom, Baby & Kids Medan, there are 15 respondents.The sampling technique used is purposive sampling. The statistical test of this study used the McNamer test. The results showed that there was an effect on the Baby spa on the quality of baby sleep in Les Bubbles Exclusive For Mom, Baby & Kids Medan with a p value = 0.031 (p <0.05).The results showed that there was an effect on the Baby spa on the quality of baby sleep in Les Bubbles Exclusive For Mom, Baby & Kids Medan with a p value = 0.031 (p <0.05). The conclusion of this study is that the Baby spa has an influence on the quality of sleep which plays a role in reducing the level of infant muscle tension so that the baby is more comfortable in resting and easy to sleep